2016
DOI: 10.1038/srep19012
|View full text |Cite
|
Sign up to set email alerts
|

Large molecular systems landscape uncovers T cell trapping in human skin cancer

Abstract: Immune surveillance of tumour cells is an important function of CD8 T lymphocytes, which has failed in cancer for reasons still unknown in many respect but mainly related to cellular processes in the tumour microenvironment. Applying imaging cycler microscopy to analyse the immune contexture in a human skin cancer we could identify and map 7,000 distinct cell surface-associated multi-protein assemblies. The resulting combinatorial geometry-based high-functional resolution led to discovery of a mechanism of T c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, since quiescent MuSCs are located underneath the basal lamina on the muscle fibers, direct cell-cell contact between MuSCs and ECs may not be possible. Interestingly, recent work from electron microscopy and imaging cycler microscopy has revealed that the basal lamina contains fractures through which cells separated by the basal lamina may communicate to each other (Koulish, J.Morphol., 1971; Hillert et al, 2016), supporting the idea that direct cell-cell interaction with the adjacent ECs is the mechanism for MuSC maintenance.…”
Section: Discussionmentioning
confidence: 66%
“…However, since quiescent MuSCs are located underneath the basal lamina on the muscle fibers, direct cell-cell contact between MuSCs and ECs may not be possible. Interestingly, recent work from electron microscopy and imaging cycler microscopy has revealed that the basal lamina contains fractures through which cells separated by the basal lamina may communicate to each other (Koulish, J.Morphol., 1971; Hillert et al, 2016), supporting the idea that direct cell-cell interaction with the adjacent ECs is the mechanism for MuSC maintenance.…”
Section: Discussionmentioning
confidence: 66%
“…The corresponding medical indication should be made as early as possible to prevent irreversible damage of the motor system. The MUSIC robotics technology and corresponding protocols have been described in detail [18]- [24]. The experiences reported here might stimulate a systematic mathematical approach to the molecular geometry of emergence mechanisms in diseases, which cannot be revealed by large scale expression profiling without anatomical resolution, as illustrated in Figure 2, on the right.…”
Section: Discussionmentioning
confidence: 96%
“…One possible explanation for this is the limited potential for additional activation of this TIL population and the existence of alternative local immune suppression pathways in tumors with effective antigen recognition, activation and T-cell migration. In this regard, diverse mechanisms have been proposed to be used by tumors to block the T-cell attack including collagen deposition around tumor cells 40 , exacerbated lysosome secretion and perforin degradation at the lytic synapse 41 , cytotoxic T-cell trapping in specific tissue compartments 42 and metabolic alterations of T-cells 43 .…”
Section: Discussionmentioning
confidence: 99%